2012
DOI: 10.5430/ijfr.v4n1p132
|View full text |Cite
|
Sign up to set email alerts
|

Risk Management Practices: A Survey of Micro-Insurance Service Providers in Kenya

Abstract: In the recent past, concerted efforts have been made to encourage financial service access to the poor starting with microfinance and subsequently micro-insurance. With complexity of insurance and the vulnerability of the target market, there are inherent risks that insurance companies face in serving the low-end market. This study documents these risks, discusses the strategies that Kenyan insurance companies are using to mitigate the risks and discerns creative strategies to minimize them. Purposive sampling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The dependent and independent variables were measured on a 5-point Likert Scale: 1= "Not at all", 2 = "to a small extent", 3 = "to a moderate extent", 4 = to a great extent, and 5= "To a very great extent" where respondents were requested to rate, in their opinion, the extent of PAM practice and microinsurance appropriateness in Tanzania based on the 5-point Likert scales above. This measurement approach was previously used by several scholars including Bergam et al (2014); Min and Mentzer (2007), and Njuguna and Arunga (2013), to evaluate the clientvalue of microinsurance products.…”
Section: Operationalization and Measurement Of Variablesmentioning
confidence: 99%
“…The dependent and independent variables were measured on a 5-point Likert Scale: 1= "Not at all", 2 = "to a small extent", 3 = "to a moderate extent", 4 = to a great extent, and 5= "To a very great extent" where respondents were requested to rate, in their opinion, the extent of PAM practice and microinsurance appropriateness in Tanzania based on the 5-point Likert scales above. This measurement approach was previously used by several scholars including Bergam et al (2014); Min and Mentzer (2007), and Njuguna and Arunga (2013), to evaluate the clientvalue of microinsurance products.…”
Section: Operationalization and Measurement Of Variablesmentioning
confidence: 99%
“…Comparing the household readiness to pay with the anticipated guarantee and insurance conveyance costs, Akter et al, (2011), showed that a standalone crop insurance scheme is likely to suffer 25% to 50% loss each year. Njuguna and Arunga (2012), finds that pricing represents significant challenges due to need to balance prices, cost, sustainability and accessibility. Regardless of whether the household has the capacity and is willing to purchase insurance depends on the level of utility expected with insurance against the utility expected without insurance (Kirigia et al, 2005).…”
Section: Factors Influencing Demandmentioning
confidence: 99%
“…Onduso (2014) conducted a research on factors influencing penetration of micro insurance in Kenya and established that low income, poor distribution channels and lack of sufficient education affected the uptake of insurance service and products. Njuguna and Arunga (2012) examined the risk management practices by service providers of micro-insurance. Njihia (2013) undertook a study on challenges of market penetration of general insurance firms in Kenya.…”
Section: Statement Of the Problemmentioning
confidence: 99%